Productive Thinking Skills among Students of the College of Education for Girls (Journal of the College of Basic Education, 2026)
The current research aims to identify the level of productive thinking skills among female students of the College of Education for Women and to examine the statistically significant differences according to the specialization variable (scientific vs. humanities). To achieve the research objectives, the researcher employed the descriptive method on a stratified random sample of (100) female students. The researcher adopted the scale developed by Abu Aziz (2020), consisting of (29) items with five response alternatives. The validity of the instrument was verified through expert review, and reliability was calculated using the split-half method corrected by the Spearman-Brown formula, yielding a reliability coefficient of (0.910). The results revealed that the students possess a high level of productive thinking skills, and that there are statistically significant differences in favor of the scientific specialization compared to the humanities specialization. The research reached a set of conclusions, recommendations, and suggestions.